1994
DOI: 10.1098/rstb.1994.0113
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte apoptosis and the control of inflammation

Abstract: We have described a novel pathway available for the clearance of extravasated granulocytes from inflamed tissues whereby aging granulocytes undergo apoptosis, a process which leads to their phagocytosis by inflammatory macrophages. By contrast with necrosis, which may also be seen at inflamed sites, apoptosis represents a granulocyte fate which by a number of mechanisms would tend to limit inflammatory tissue injury and promote resolution rather than progression of inflammation: (i) apoptosis is responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(82 citation statements)
references
References 25 publications
2
79
1
Order By: Relevance
“…Neutrophils are short-lived, but a central component of their responses to pathogens includes the prolongation of their life span (21). Our work also showed that neutrophil responses to TLR ligands were, in part, mediated by monocytes that commonly contaminate leukocyte preparations (20).…”
mentioning
confidence: 57%
“…Neutrophils are short-lived, but a central component of their responses to pathogens includes the prolongation of their life span (21). Our work also showed that neutrophil responses to TLR ligands were, in part, mediated by monocytes that commonly contaminate leukocyte preparations (20).…”
mentioning
confidence: 57%
“…Aberrations in either mechanism are associated with chronic inflammatory conditions and autoimmune disorders [13][14][15]. Uptake of apoptotic cells by phagocytes is thought to suppress autoimmune responses through the release of anti-inflammatory cytokines IL-10, TGF-β, platelet activating factor (PAF), and prostaglandin E 2 (PGE 2 ), and inhibition of proinflammatory cytokines TNF-α, GM-CSF, IL-12, IL-1β, and IL-18 [16][17][18].…”
Section: Phagocytosis Of Apoptotic Cells and Regulation Of Immune Resmentioning
confidence: 99%
“…Aberrations in either mechanism are associated with chronic inflammatory conditions and autoimmune disorders. [40][41][42] Uptake of apoptotic cells by phagocytes is thought to suppress autoimmune responses through the release of anti-inflammatory cytokines IL-10, transforming growth factor-b, platelet-activating factor and prostaglandin E 2 , and inhibition of proinflammatory cytokines TNF-a, granulocyte-macrophage colony-stimulating factor, IL-12, IL-1b and IL-18. [43][44][45] Our group recently has shown that during phagocytosis by macrophages, apoptotic cell-derived signals trigger dephosphorylation and activation of a novel nuclear zinc finger-like protein, named GC-binding protein, which targets a specific site in the IL-12 p35 gene promoter, preventing its transcription.…”
Section: Introductionmentioning
confidence: 99%